Malonyl CoA Decarboxylase Inhibition Improves Cardiac Function Post-Myocardial Infarction - Wei Wang, MD, PhD; Liyan Zhang, PhD; Pavan K. Battiprolu, PhD; Arata Fukushima, MD, PhD; Khanh Nguyen, BS; Kenneth Milner, BS; Abhishek Gupta, PhD; Tariq Altamimi, PhD; Nikole Byrne, BS; Jun Mori, MD, PhD; Osama Abo Alrob, PhD; Cory Wagg; et al. (JACC: Basic to Translational Science, 2019)
Summary: Alterations in cardiac energy metabolism after a myocardial infarction contribute to the severity of heart failure (HF). Although fatty acid oxidation can be impaired in HF, it is unclear if stimulating fatty acid oxidation is a desirable approach to treat HF. Both immediate and chronic malonyl coenzyme A decarboxylase inhibition, which decreases fatty acid oxidation, improved cardiac function through enhancing cardiac efficiency in a post–myocardial infarction rat that underwent permanent left anterior descending coronary artery ligation. The beneficial effects of MCD inhibition were attributed to a decrease in proton production due to an improved coupling between glycolysis and glucose oxidation. Key Words: fatty acid oxidation, heart failure, glucose oxidation, uncoupling of glycolysis